Simulation System Design Methodology in Extended Enterprise Context. Issue 4 (12th January 2022) - Leroux‐Beaudout, Renan; Bruel, Jean‐Michel; Ober, Ileana; Pantel, Marc
ABSTRACT: The use of Model‐Based Systems Engineering and early Verification and Validation through simulations offers an effective way to manage the complexity of real‐world industrial development projects. However, the modeling and simulation activities are often conducted in parallel, based on a common core of requirements. This can lead to a product model that does not conform to the simulation model, and vice versa, due to potential misinterpretation of requirements. To fill this gap and meet the objective of the simulation conformed to the model, we propose a new approach that considers communication between stakeholders of the Extended Enterprise and also between the simulations platforms.